(untitled) (Musytari : Jurnal Manajemen, Akuntansi, dan Ekonomi, 2025)
This study focuses primarily on the determination of production cost using the process costing method at BCL Konveksi, a manufacturing company. Accurate calculation of production costs is crucial to assist the company in setting appropriate selling prices, thereby achieving the desired profit. The research indentified discrepancies in cost details that were previously unaccounted for, which affected suboptiomal pricing decisions. By applying the process costing method, this study recalculated and found the total production cost to be IDR 316.910.111,11 for 12.000 units, with a cost per unit of IDR 26.409,18. This process-based costing method provides superior results in detailed and structured cost management.